2002
DOI: 10.1300/j070v11n02_05
|View full text |Cite
|
Sign up to set email alerts
|

The Colorado Sex Offender Risk Scale

Abstract: This study documents the development of an adult sex offender risk assessment tool. A sample of 494 sex offenders were followed for an average of 30 months. A risk scale was developed based upon criminal and therapeutic outcomes. The final risk scale included prior juvenile felony convictions, prior adult felony convictions, failure of the first or second grade, not being employed, victim being intoxicated, the perpetrator reporting not being sexually aroused during the crime, possession of a weapon during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Ruback and Ivie (1998) examined information about the rapes of 2526 adult females from the records of a rape crisis centre, finding that attacks by strangers were more likely to involve a weapon and to occur outdoors than were attacks by nonstrangers and victims were less likely to physically resist strangers than non strangers. English, Retzlaff and Kleinsasser (2002) developed the Colorado Sex Offender Risk Scale. A sample of 494 sex offenders was followed for an average of 30 months.…”
Section: Weapon Use In the Mentally Disorderedmentioning
confidence: 99%
“…Ruback and Ivie (1998) examined information about the rapes of 2526 adult females from the records of a rape crisis centre, finding that attacks by strangers were more likely to involve a weapon and to occur outdoors than were attacks by nonstrangers and victims were less likely to physically resist strangers than non strangers. English, Retzlaff and Kleinsasser (2002) developed the Colorado Sex Offender Risk Scale. A sample of 494 sex offenders was followed for an average of 30 months.…”
Section: Weapon Use In the Mentally Disorderedmentioning
confidence: 99%
“…Unfortunately, among other concerns with the study, the outcome used in English et al (2002) confounded treatment attrition and sexual recidivism (see also Maletzky, 1993), making it impossible to determine the independent relationship of denial with either. However, the findings support a link between denial and failure to complete treatment, and also provide grounds for postulating that more comprehensive indices of denial (and minimization) would account for a unique portion of the variance in sexual recidivism in multivariate models.…”
Section: Treatment Completion Status Psychopathic Traits and Sex Ofmentioning
confidence: 99%
“…Among a sample of 204 juvenile sex offenders referred to a community-based treatment program, Hunter and Figueredo (1999) found that self-reported level of defensiveness/denial was found to decrease the chances of remaining in and/or completing the program (see also Beyko & Wong, 2005). English et al (2002) reported additional evidence of the association between denial and negative outcomes among 494 adult sex offenders (54% of whom were in the community). Their denial variable was an 8-item scale (α = .93; e.g., denies actual facts of offense, blames others for the crime, says therapy is unnecessary).…”
Section: Treatment Completion Status Psychopathic Traits and Sex Offender Type As Potential Confoundsmentioning
confidence: 99%
See 1 more Smart Citation